Protocol for a randomized controlled trial of electroacupuncture in the management of patients with axial spondyloarthritis in Singapore (E‐AcuSpA) - Warren Fong; Yu Heng Kwan; Su‐An Quek; Ader Lim; Chiah Yuen Wong; Shin Yoong Chua; Hui Chin Tan; Clara Eng; Choy Tip Tan; Bao Qiang Dong; Youyi Huang; Chuen Seng Tan; et al. (Rheumatology & Autoimmunity, 2021)
Abstract Background Despite therapeutic advances, treatment of patients with axial spondyloarthritis (axSpA) continue to pose as a challenge as many do not respond well to conventional Western medications, such as nonsteroidal anti‐inflammatory drugs (NSAIDs) and biologic disease‐modifying antirheumatic drugs (bDMARDs). Hence, acupuncture is a possible alternative. Some studies found electroacupuncture to be better than manual acupuncture, though no trials have been conducted in patients with axSpA. This clinical trial aims to evaluate the clinical efficacy, safety, and cost‐effectiveness of electroacupuncture compared to manual acupuncture for patients with axSpA. Methods/Design This randomized controlled trial will recruit 100 patients diagnosed with axSpA, who have active disease despite NSAIDs and bDMARDs. Eligible patients will be randomized to receive either electroacupuncture or manual acupuncture in a 1:1 ratio. All participants will receive standard rheumatologic care in addition to 20 acupuncture sessions. The mean difference in Bath Ankylosing Spondylitis Disease Activity Index score between the 2 groups over 12 weeks will serve as the primary outcome. Secondary outcomes include improvements in other clinical, quality of life, and economic outcomes over 24 weeks. All adverse events will be recorded. Discussion Results from this trial may provide evidence regarding the clinical effectiveness, safety, and cost‐effectiveness of electroacupuncture compared to manual acupuncture for patients with axSpA, and guide implementation into clinical practice. Limitations of this trial include the lack of patient blinding, use of a repeated measures design, and possible variation in acupuncture technique amongst the various Traditional Chinese Medicine practitioners.